Effect of Industrial Design Management and Innovation on Business Performance: An Empirical Evidence of Malaysian Industrial Product Companies - Al-Shorman, Mohammad; Alshorman, Qusi Hassan; Alharahsheh, Suhaib Ahmed; Tbeishat, Habeeb (International Journal of Psychosocial Rehabilitation, 2020)
Due to the growth of Industial design management and innovation value in creating a sustainable competitive advantage, few studies have been done to quantify the contribution of industrial design management and innovation towards business performance. This study applied PLS Structural equation modeling (PLS-SEM) method to analyze the effect of industrial design management and innovation on business performance of Malaysian industrial product companies. A total of 450 responses from the employees were obtained but only 400 valid responses were used for the analysis. The results revealed that industrial design management and innovation have an influence on the business performance of Malaysian industrial product companies. The path coefficient of industrial Design Management and Business Performance is 0.783387. Moreover, the path coefficient of Innovation and Business Performance is 0.123332 and the result of R2 is 0.757063. The finding also showed that industrial design management and innovation have positive and significant relationship with the business performance of Malaysian industrial product companies. Therefore, the findings of the study will guide the industrial product companies to focus on industrial design management and innovation processes that needed to be improved in order to expedite the business performance.